PREPARATION AND CHARACTERIZATION OF PHYSICO-MECHANICAL AND STRUCTURAL PROPERTIES OF PHTHALIMIDE DERIVATIVE POLYMERIC NANOCOMPOSITES - Bilici, Vildan Özkan; Kaya, Esin (Vinca Inst Nuclear Sci, 2022)
In this study, phthalimide derived polymer-TiO2 nanocomposites were prepared by direct mixing method and their mechanical properties were compared. The high content filler polymer nanocomposites with sufficient interface bonding with the polymer matrix have been prepared to maximize the properties of the filler. In the direct mixing method, the polymer obtained by free radical polymerization of the monomer was mixed with TiO2 in high weight percentages. The pulse-echo method was used to characterize the elastic constants of the polymer and polymer-TiO2 nanocomposites through detection of the ultrasonic waves. Transverse and longitudinal ultrasonic velocities have been used to calculate Young's modulus of these samples. The ultrasonic velocity and Young's modulus values of polymer-TiO2 nanocomposites showed a linear relationship with the weight percentage of the polymer, which is due to the strong and effective interaction between the particles resulting from by reinforcing TiO2 to the polymer structure. The clustering that emerged with the increase in the amount of reinforcement in the SEM images became more pronounced and it was observed that pure polymer and TiO2 were homogeneously distributed. The porosity and hardness measurements of the polymer and polymer-TiO2 nanocomposites were examined. The hardness and porosity of the polymer structure approximately increased as the percentage values of TiO2 increased. Moreover, TGA results of polymer nanocomposites obtained by direct mixing showed that the thermal stability increased linearly as the weight ratio increase of TiO2 in comparison with the pure polymer.
Keywords: nanocomposite polymers; polyphthalimide; young's modulus; ultrasonic non-destructive testing; porosity; hardness; Composites; Microstructure; Dispersion; Modulus